solve for x: 6x^2 -9x + 1=0

Question

Asked 12/14/2013 9:09:00 PM

Updated 6/3/2014 3:06:38 AM

1 Answer/Comment

Flagged by yeswey [6/3/2014 3:06:38 AM]

Question

Asked 12/14/2013 9:09:00 PM

Updated 6/3/2014 3:06:38 AM

1 Answer/Comment

Flagged by yeswey [6/3/2014 3:06:38 AM]

Rating

3

6x^2 - 9x + 1 = 0

b^2 - 4ac = (-9)^2 - 4(6)(1) = 81 - 24 = 57

x = [-b ± sqrt (b^2 - 4ac)]/2a

= (9 ± sqrt 57)/12

b^2 - 4ac = (-9)^2 - 4(6)(1) = 81 - 24 = 57

x = [-b ± sqrt (b^2 - 4ac)]/2a

= (9 ± sqrt 57)/12

Added 6/3/2014 3:06:35 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/3/2014 2:34:21 PM]

compute the value of the discriminant and give the number of real solutions of the quadratic equation: -8x^2 + 3x + 2=0

Question

Expert Answered

Updated 7/27/2014 3:41:31 PM

1 Answer/Comment

-8x^2 + 3x + 2=0

Discriminant:

b^2 - 4ac

= (3)^2 - 4(-8)(2)

= 9 + 64

= 73, two irrational solutions.

Discriminant:

b^2 - 4ac

= (3)^2 - 4(-8)(2)

= 9 + 64

= 73, two irrational solutions.

Added 7/27/2014 3:41:30 PM

This answer has been confirmed as correct and helpful.

27,089,026

questions answered

There are no comments.